Schein's common sense emergency abdominal surgery - Schein, Moshe; Rogers, Paul N.; Leppaniemi, Ari; Rosin, Danny; Efron, Jonathan E. (Tfm Pub., 2016)
This is a great book for surgical training. It distills much common sense regarding emergency abdominal surgery using a simple and easy-to-understand approach. It is highly recommended reading for all surgical trainees.